Cult Spaces. Preliminary Thoughts on the Temple of Artemis at Amarynthos (Euboea, 8th-6th Centuries BCE) - Verdan, Samuel; Saggini, Tamara; André, Jérôme; Kyriazi, Olga; Theurillat, Thierry (ARYS. Antigüedad: Religiones y Sociedades, 2025)
The Sanctuary of Artemis Amarysia at Amarynthos was the most prominent extra-urban sanctuary of the ancient city of Eretria, on the island of Euboea. The precise location of the site has only recently been identified, and it has since been the focus of extensive excavations, with particular attention given in recent years to the temple area. A series of edifices were constructed there atop one another over a long period spanning from the end of the Bronze Age to the end of the Archaic period. What appears to be the first temple was erected at the end of the 8th century BCE and remained in use for about two centuries. This monumental building was divided into three rooms, each housing one or more fireplaces/altars. The article offers some preliminary thoughts on these specific architectural layout and associated facilities, which offer insights into the activities that took place inside the temple. While substantial evidence for animal sacrifice has been uncovered, it is not yet clear whether the fireplaces/altars were used for successive stages of the same sacrifice, or for distinct rituals performed on separate occasions. Furthermore, the question of the function of the rear room – possibly an adyton – is also discussed. The 8th-century temple at Amarynthos provides a valuable case study for understanding the organisation of sacred space and ritual practices at a time when religious architecture was developing in Greece.